Analisis Analisis Pemahaman Pajak Penghasilan Dan Sanksi Pajak Pada Wajib Pajak Pribadi Karyawan PT. Bina Artha Ventura - Arif Rakhman; Risyaf, Muhammad (The Double Entry Journal, 2023)
General society adds to the state depository through charges which are utilized to fund state consumption and in view of enforceable regulations. Charges are paid without getting equal administrations that can be demonstrated straightforwardly (counter execution). This exploration means to dissect the comprehension of pay endlessly charge sanctions on individual citizens of PT representatives. Bina Arta Ventura. This exploration is quantitative examination, and the information source got is essential information. The example for this examination was 50 workers at PT. Bina Adventure. Information examination utilizes numerous direct relapse investigation. The consequences of the exploration show that in a halfway test, understanding personal duty affects individual citizens at PT. Bina Arta Ventura, charge sanctions influence individual citizens. In view of a concurrent trial of understanding pay endlessly charge endorses, the impact on worker individual citizens. With a coefficient of assurance (R square) of 0.771, and that implies that concurrent comprehension of pay endlessly charge approvals can make sense of 77.1% of individual citizens at PT. Bina Arta Ventura and the rest are affected by different factors outside the examination.